Menganalisis Kebutuhan Dan Kecenderungan Neurotik Tokoh Re: Dalam Novel “RE: Dan Perempuan” Karya Maman Suherman - Aprilia Sindi Mayasari; Dinda Nalurita A.; Eva Dwi Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out, analyze and describe the needs and tendencies of Re: in the novel Re: and peRempuan by Maman Suherman. The formulation of the problem in this study is what are the neurotic needs and tendencies experienced by the character Re:. The method in this research uses qualitative research and descriptive method. The result of this research is that the character Re: has 3 neurotic needs, namely, 1) the neurotic need for affection and self-acceptance, 2) the neurotic need to limit his life in a narrow scope, 3) the neurotic need for independence and freedom. And has 3 neurotic tendencies namely, 1) approaching others, 2) fighting others, 30) avoiding others.